Saving time and effort: Best practice for adapting existing patient-reported outcome measures in hepatology - Hayley Hutchings (World Journal of Hepatology, 2022)
It is increasingly recognised that collecting patient reported outcome measures (PROMs) data is an important part of healthcare and should be considered alongside traditional clinical assessments. As part of a more holistic view of healthcare provision, there has been an increased drive to implement PROM collection as part of routine clinical care in hepatology. This drive has resulted in an increase in the number of PROMs currently developed to be used in various liver conditions. However, the development and validation of a new PROM is time-consuming and costly. Therefore, before deciding to develop a new PROM, researchers should consider identifying existing PROMs to assess their appropriateness and, if necessary, make adaptations to existing PROMs to ensure their rigour when used with the target population. Little is written in the literature on how to identify and adapt the existing PROMs in hepatology. This article aims to provide a summary of the current literature and guidance regarding identifying and adapting existing PROMs in clinical practice.